Social interactions in the workplace in the light of the social exchange theory: (Revista Brasileira Multidisciplinar, 2023)
Abstract: Workplace relationships, according to social exchange theory, offer a perspective for understanding how people interact and develop relationships with their supervisors and colleagues. Thus, the present study aimed to systematize the empirical literature that relates social exchange theory in the organizational context. To this end, a search was conducted in the main databases (Scopus and Web of Science) to analyze the research published in this context based on the use of the 4W’s model of Rosado-Serrano, Paul and Dikova (2018). 73 publications were identified that met the inclusion criteria, and 25 of these were selected for the present review, evidencing the existence of studies that corroborate about the subject. As a result, among the social interactions most cited by scholars, pillars that positively affect work relationships, such as commitment, loyalty and trust of employees towards the organization, and arouse in employees organizational citizenship behavior, job satisfaction, effective performance, support and organizational justice, among others, stand out. This study not only reinforces the relationships and relevance of social exchange theory, but also provides empirical support for understanding the experiences and relationships between employees and their supervisors or colleagues, as well as extends the body of research on organizational behavior.
Keywords: organizational behavior; social interaction; social exchange theory